A Study of Bicycle Helmet Use and Bicycle Safety In Dublin - Murad, Faris (Trinity Student Medical Journal, 2001)
Introduction: Cycling continues to be popular among children, but it also associated with a significant number of injuries and deaths. The majority of deaths are due to head injuries and are therefore emminently preventable. Aim: To study bicycle helmet use and attitudes in children age 8-18 years in the Dublin area. Methods: A ques- tionnaire was distributed to 6 schools in the suburbs of Dublin (St. Mary’s College; Muckross Park College, Mt. Anville College and Jr. School, St. Mary’s National School, and Sandford Park School). Permission was obtained from the corresponding principal for each school. The survey consisted of 8 questions that were used to assess the use and attitudes towards bicycle safety and helmet use. The data was compiled and an analysis of trends between groups was established. Results: 1230 children aged 8-18 returned completed questionnaires. The results were analysed comparing gender and age. Among children 8-11 years who owned a helmet, around 35% did not wear their helmet. Whereas in boys and girls aged 12-18 years who owned a helmet, around 58% claimed to never wear their helmet. Implementing a law requiring helmet use would have little impact on children 12-18 years (decrease in non-compliance from 58% to 44%). However, legislation would have a greater impact on chil- dren aged 8-11 years (decreasing non-compliance from 29% to 16%. Conclusions: Helmets are an important form of prevention of head injury among bicycle riders. Health promotion programs in Ireland should focus on bicycle safety education, helmet use, and the adoption of legislation requiring the use of bicycle helmets. Targeting children 8-11 years old will have the greatest impact in the long run, which will hopefully lead to a decrease in the number of bicycle related fatalities. TSMJ 2001, vol 2, 59-61.